Development and heating systems mathematical model of heat and mass transfer in the greenhouse with alternative energy sources - Gorobec, V.; Yatsenko, O. (Energy and Automation, 2015)
The proposed project equipment heating greenhouses solar collectors and heat pumps. Simulations of processes of heat and mass transfer in the greenhouse. Simulations performed using software environment ANSYS Fluent 14.0. The result obtained velocity field and temperature in the greenhouse.